2018
DOI: 10.1002/jeab.462
|View full text |Cite
|
Sign up to set email alerts
|

A laboratory model for evaluating relapse of undesirable caregiver behavior

Abstract: The success of behavioral treatments like functional communication training depends on their continued implementation outside of the clinical context, where failures in caregiver treatment adherence can lead to the relapse of destructive behavior. In the present study, we developed a laboratory model for evaluating the relapse of undesirable caregiver behavior that simulates two common sources of disruption (i.e., changes in context and in treatment efficacy) believed to affect caregiver treatment adherence us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 48 publications
(72 reference statements)
3
62
1
Order By: Relevance
“…Thus, instances of resurgence may result in more sustained increases in destructive behavior when routine caregivers implement reinforcement schedule thinning, because they may be less likely to implement extinction with high integrity during such periods. That is, caregivers may be more likely than highly trained behavior therapists to deliver the functional reinforcer in response to an instance of resurgence, which would likely sustain resurgence (Bruzek, Thompson, & Peters, ; Mitteer, Greer, Fisher, Briggs, & Wacker, in press; St. Peter Pipkin, Vollmer, & Sloman, ). Future research should examine whether and to what extent caregivers show decreased procedural integrity when implementing reinforcement thinning steps that produce resurgence relative to thinning steps that do not evoke resurgence.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, instances of resurgence may result in more sustained increases in destructive behavior when routine caregivers implement reinforcement schedule thinning, because they may be less likely to implement extinction with high integrity during such periods. That is, caregivers may be more likely than highly trained behavior therapists to deliver the functional reinforcer in response to an instance of resurgence, which would likely sustain resurgence (Bruzek, Thompson, & Peters, ; Mitteer, Greer, Fisher, Briggs, & Wacker, in press; St. Peter Pipkin, Vollmer, & Sloman, ). Future research should examine whether and to what extent caregivers show decreased procedural integrity when implementing reinforcement thinning steps that produce resurgence relative to thinning steps that do not evoke resurgence.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to studies that evaluated operant renewal as a singular relapse phenomenon, we also included preparations that combined contextual changes with other variables commonly associated with relapse (e.g., the resurgence of maladaptive behavior as a result of decrements in reinforcement for a newly taught alternative response). We included these studies because combined relapse arrangements may better simulate what occurs in practice when multiple environmental events interact during relapse (e.g., Mitteer, Greer, Fisher, Briggs, & Wacker, ). We excluded studies that (a) examined operant renewal using nonhuman animal subjects, (b) examined renewal in a respondent conditioning paradigm with humans, (c) described simple failures of generalization across environments or contexts (e.g., Schindler & Horner, ), (d) did not report or display data at the individual level, and (e) were reviews, meta‐analyses, book chapters, or dissertations.…”
Section: Methodsmentioning
confidence: 99%
“…Briggs et al (2018) found that resurgence is common when using FCT-at least one episode of resurgence in over 75% (19/25) of FCT applications during reinforcementschedule thinning. In addition, Mitteer, Greer, Fisher, Briggs, and Wacker (2018) trained caregivers to implement FCT with high integrity and examined the conditions under which resurgence of undesirable caregiver behavior occurred, with undesirable caregiver behavior including reinforcement of destructive behavior. Mitteer et al found that caregiver reinforcement of destructive behavior increased when desirable caregiver behavior (i.e., implementing treatment) had no effect on destructive behavior during a context change.…”
mentioning
confidence: 99%